Humanization in health: A look at the Radiotherapy (Research, Society and Development, 2024)
In the context of radiotherapy, not only is knowledge necessary, but also humanized practice, between professionals and patients, needs to evolve and receive greater attention. However, there are issues to be analyzed regarding health education in Brazil: are humanization practices being considered in the literature as research for improving radiotherapy treatment? Are technicians being pedagogically prepared to practice humanized care? The objective of the research is to analyze how humanization is being addressed for the development of new research and for the training of technicians and/or technologists in radiotherapy. In order to identify general productions on the topic of humanization in Brazil from 2013 to 2023, a Systematic Literature Review was conducted; using the following combinations: "humanization" and "National Humanization Policy," "humanization" and "health," "humanization" and "nursing," "humanization" and "radiology," "humanization" and "radiotherapy." Considering the small number of works, there is a need to further explore the topic, both in professional training and in research.